Pengaruh Word of Mouth, Harga dan Kualitas Pelayanan Terhadap Keputusan Pembelian Pada Toko Bangunan Sidik Putra Selong Lombok Timur - Rahmawati, Dian; Retnowati, Weni; Widiana, Harmi (Postgraduate, University of Mataram, 2025)
This study aims to determine the effect of word of mouth, price and service quality on purchasing decisions at the Sidik Putra Selong Building Shop, East Lombok. The type of research used is associative research. The sample in this study amounted to 100 samples. The data collection method uses a survey method. The sample collection technique in this study used non probability sampling technique with purposive sampling method. Data analysis in this study used multiple linear regression analysis to prove the research hypothesis. All research data were obtained using SPSS Statitic 26. It is obtained: (1) Word of Mouth has a positive and significant effect on purchasing decisions, (2) Price has a positive and significant effect on purchasing decisions, (3) Service quality has a positive and significant effect on purchasing decisions. So it is concluded that the more positive the word of mouth, the higher the purchasing decision will be, otherwise if the word of mouth is negative, the lower the purchasing decision will be. The more appropriate the price, the higher the purchasing decision will be, otherwise if the price is not appropriate, the lower the purchasing decision will be. The more appropriate the service quality, the higher the purchasing decision will be, otherwise if the service quality is not appropriate, the lower the purchasing decision will be.